2018
DOI: 10.1159/000492576
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Induces Osteoblastic Differentiation of Mesenchymal Stem Cells and Promotes Fracture Healing in a Rat Model of Femoral Fracture via Neuropeptide Y/Neuropeptide Y Receptor Y1 Signaling

Abstract: The function of melatonin (MLT) in promoting fracture healing has been demonstrated in previous studies. However, the molecular mechanism underlying therapeutic effects of MLT is not entirely clear. In this study, mesenchymal stem cells (MSCs) were isolated from rat bone marrow and identified by flow cytometry. We found that MLT treatment upregulated the neuropeptide Y (NPY) and NPY receptor Y1 (NPY1R) expression, and promoted the proliferation and migration of MSCs, which was suppressed by BIBP3226, an inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…However, melatonin‐induced osteoblast differentiation of MSC was suppressed by BIBP3226 (an inhibitor of NPY1R), as evidenced by decreased levels of alkaline phosphatase (ALP), collagen type I α1 chain, osteocalcin, and runt‐related transcription factor 2. This result suggests that melatonin promotes osteoblast differentiation of MSC via NPY/NPY1R signaling . Preconditioning of melatonin predominantly reduces the expression of Bax but increases the expression of Bcl2 in bone marrow‐derived MSC (BMSC).…”
Section: Mechanisms Underlying Melatonin's Action On Osteoporosismentioning
confidence: 97%
See 1 more Smart Citation
“…However, melatonin‐induced osteoblast differentiation of MSC was suppressed by BIBP3226 (an inhibitor of NPY1R), as evidenced by decreased levels of alkaline phosphatase (ALP), collagen type I α1 chain, osteocalcin, and runt‐related transcription factor 2. This result suggests that melatonin promotes osteoblast differentiation of MSC via NPY/NPY1R signaling . Preconditioning of melatonin predominantly reduces the expression of Bax but increases the expression of Bcl2 in bone marrow‐derived MSC (BMSC).…”
Section: Mechanisms Underlying Melatonin's Action On Osteoporosismentioning
confidence: 97%
“…This result suggests that melatonin promotes osteoblast differentiation of MSC via NPY/NPY1R signaling. 76 Preconditioning of melatonin predominantly reduces the expression of Bax but increases the expression of Bcl2 in bone marrow-derived MSC (BMSC). In addition, melatonin promotes osteogenesis through increasing osteocalcin expression, thereby inhibiting bone loss, suggesting that melatonin may be a potential target for osteoporosis.…”
Section: Melatonin Promotes Osteogenesis In Osteoblastsmentioning
confidence: 99%
“…Another interesting finding of Dong P and his colleagues is that melatonin promotes osteoblastic differentiation of MSCs and fracture healing in rats with femoral fracture via NPY/NPY1R signaling 31 .…”
Section: Resultsmentioning
confidence: 99%
“…Melatonin positively regulates Runx2 in many cells and tissues, such as osteogenic and chondrogenic differentiation of human MSCs, osteoblastic differentiation of MSCs from rats, co‐culture models (transwell or layered) of human MSCs and peripheral blood monocytes, human osteosarcoma‐derived Saos2 cells, human periodontal ligament cells and cementoblasts, osteogenic potential of platelet‐rich plasma in dental stem‐cell cultures, the differentiation of mouse osteoblastic MC3T3‐E1 cells, primary bone marrow MSCs from ovariectomized mice, bovine ovarian granulosa cells, a blind mouse model (MMTV‐Neu transgenic mice), and pinealectomized or ovariectomized rats. Our study further confirmed that there was no direct interaction between melatonin and Runx2 although melatonin directly penetrates cytomembrane and enters the cell nucleus where it could bind to Runx2.…”
Section: Discussionmentioning
confidence: 99%